(خصائص المنهج القرآني في بناء الإنسان والحضارة عند ابن عاشور من خلال التحرير والتنوير: (دراسة موضوعية: The Characteristics of The Qur’anic Approach in Human and Civilization Building According to Ibn Achour in His Book Al-Tahrir Wa Tanwir: Thematic Study - Hocini, Mohamed Amine; Abdullah, Mustaffa; Bounama, Fouad; Benabidi, Mohamed Tahar (Online Journal of Research in Islamic Studies, 2019)
This research aims to clarify the characteristics of the Qur’anic approach in human and civilization building according to Ibn Achour in his Book Al-Tahrir wa Al-Tanwir. The problem statement of this research is that the characteristics of the Qur’anic approach as mentioned in Al-Tahrir wa Al-Tanwir need to be identified, highlighted and analyzed. This study is significant because it identifies and uncovers the characteristics of the Qur’anic approach in human and civilization building according to the Ibn Achour in his Tafsīr, which is essential to qualify the human being to fulfill the duties he is assigned with. This research used the inductive and the analytical approaches. The findings of the research show that the characteristics of the Qur’anic approach in human and civilization building according to Ibn Achour in his Book Al-Tahrir wa Al-Tanwir consist of five characteristics, namely: al-Fiṭra (Human instinct), al-Dawām (permanency, continuity), wa al-umūm (validity for all times and places), al-Shumūl (comprehensiveness), wa al-takāmul (integration), al-Taysīr (softness, facilitation) and finally al-Tadarruj (gradation). These characteristics are fundamentally based on Fiṭra (Human instinct).